Frequency and prognostic value of cutaneous molecular residual disease in mycosis fungoides: a prospective multicentre trial of the Cutaneous Lymphoma French Study Group. (1st October 2015) - Hurabielle, C.; Ingen‐Housz‐Oro, S.; Ortonne, N.; Cornillet‐Lefèbvre, P.; Merah, A.; D'Incan, M.; Joly, P.; Franck, N.; Estève, E.; Maubec, E.; Grange, F.; Machet, L.; et al.
Summary: Background: Monoclonal T‐cell receptor (TCR) rearrangement is detected in 57–75% of early‐stage mycosis fungoides (MF) at diagnosis. A retrospective study showed molecular residual disease (MRD) in 31% of patients in complete clinical remission (CR) after 1 year of treatment. Objectives: To confirm the frequency of MRD at 1 year and to determine its prognostic value for further relapse. Methods: Patients with T1‐, T2‐ or T4‐stage MF were prospectively included in this multicentre study. At diagnosis, clinical lesions and healthy skin were biopsied. After 1 year of topical treatment, previously involved skin of patients in CR was biopsied for histology and analysis of TCR‐γ gene rearrangement. The results were compared with the clinical status each year for 4 years. Results: We included 214 patients, 133 at T1, 78 at T2 and three at T4 stage. At diagnosis, 126 of 204 cases (61·8%) showed TCR clonality in lesional skin. After 1 year, 83 of 178 patients (46·6%) still being followed up were in CR and 13 of 63 (21%) showed MRD. At 4 years, 55 of 109 patients (50·5%) still being followed up were in CR and 44 of 109 (40·4%) were in T1 stage. MRD did not affect clinical status at 4 years (CR vs. T1/T2, P = 1·0; positive predictive value 36·4%; negative predictive value 67·6%). Conclusions: T‐cell clonality at diagnosis and MRD at 1 year are not prognostic factors of clinical status at 4 years.